Influence of Groundnut Shell Powder on Normal Concrete's Split Tensile Strength - Samsunan Samsunan; Fitria Husna Putri; Inseun Yuri Salena; Andrisman Satria (International Journal of Engineering, Science and Information Technology, 2023)
Groundnut shell powder contains significant amounts of the chemical silica (SiO) to be utilized as construction materials. Through the use of groundnut shell powder, this study seeks to determine the split tensile strength of concrete (GSP). With a compressive strength design of f'c =21.7 MPa, the concrete mixture adheres to ACI 2I1.1-91. The aggregate of crushed stone with a maximum diameter of 19.1 mm. Portland cement type I is the type of cement utilized. With a variation of 0%, 5%, 7,5%, 10%, and 12.5%, additional material (GSP) substitutes cement in part. At 14 and 28 days old, concrete is tested for its tensile strength. For each modification, there are three cylindrical test objects, each measuring 30 cm in length and 15 cm in diameter. The split tensile strength of concrete was tested using 14-day-old peanut shell powder, and the results were 1,699 MPa, 1,840 MPa, 1,581 MPa, and 1,510 MPa, respectively. The findings demonstrated that concrete's split tensile strength (f'ct) was 28 days with a fluctuation of 0%; 5%; 7,5%; 10%; and the sequential 12.5% was 1,934; 2,170; 2.265; 1,958; and 1,887 Mpa. Following the findings, the ideal tensile strength value was at a variation of 7.5%, or 2,265 MPa, greater than 0% (1,934 MPa) of 17.11%. The age of 28 days was 7.5% higher than the age of 14 days (1,840 MPa) of 23.10% for the variation's maximum tensile strength. Compared to standard compressive strength test findings, the Split tensile strength value of concrete utilizing GSP is 6.83%